2012
DOI: 10.1002/smll.201201528
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Downregulate Interleukin‐1β‐Induced Pro‐Inflammatory Responses

Abstract: Interleukin 1 beta (IL-1β)-dependent inflammatory disorders, such as rheumatoid arthritis and psoriasis, pose a serious medical burden worldwide, where patients face a lifetime of illness and treatment. Organogold compounds have been used since the 1930s to treat rheumatic and other IL-1β-dependent diseases and, though their mechanisms of action are still unclear, there is evidence that gold interferes with the transmission of inflammatory signalling. Here we show for the first time that citrate-stabilized gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
126
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 26 publications
5
126
0
1
Order By: Relevance
“…For the PVA-NH 2 AuNPs this can be associated to the increased level of cytotoxicity that they caused to the MDDCs. Yet, for the other AuNPs these findings could be attributed to recent research by Wu et al 45 who demonstrated that IL-1β is down-regulated on LPS-stimulated murine microglial cells by the addition of 10 μg/mL iron oxide NPs, via the secretory lysosomal pathway of cytokine processing, as well as Sumbayev et al 46 who reported IL-1β down-regulation to be associated with aggregation of IL-1β molecules around the surface of the NP. Interestingly, the augmentation of the IL-1β secretion was only found for (PEG + PVA)-NH 2 AuNPs at 100 μg/mL.…”
mentioning
confidence: 97%
“…For the PVA-NH 2 AuNPs this can be associated to the increased level of cytotoxicity that they caused to the MDDCs. Yet, for the other AuNPs these findings could be attributed to recent research by Wu et al 45 who demonstrated that IL-1β is down-regulated on LPS-stimulated murine microglial cells by the addition of 10 μg/mL iron oxide NPs, via the secretory lysosomal pathway of cytokine processing, as well as Sumbayev et al 46 who reported IL-1β down-regulation to be associated with aggregation of IL-1β molecules around the surface of the NP. Interestingly, the augmentation of the IL-1β secretion was only found for (PEG + PVA)-NH 2 AuNPs at 100 μg/mL.…”
mentioning
confidence: 97%
“…57 IL-1 signaling is the major alarm mechanism that persists in a tumor microenvironment, and IL-1 is produced by cells in a malignant or micro environment. This signaling has contrasting roles, such as the control and promotion of tumors, and these roles are mediated by two important agonists called IL-1a and IL-1b, respectively.…”
mentioning
confidence: 99%
“…A novel way to study the role of gold and its interaction with the immune system could be to use AuNPs, since their path can be easily followed and they can be visualized using electron microscopy methods. Citrate-coated AuNPs are more compatible with biological systems compared to other functionalized AuNPs and metallic nanoparticles such as silver 3 . They are also easy to synthesize in a wide range of monodispersed sizes from 5 to 50 nm, some of which are currently undergoing clinical tests for the treatment of different kinds of tumours 4 .…”
mentioning
confidence: 99%
“…In a recent study, we showed that AuNPs downregulate interleukin-1-Beta-dependent inflammatory responses, which are associated with many autoimmune disorders such as rheumatoid arthritis or psoriasis 3 . The anti-inflammatory activity of AuNPs was shown to most probably be due to extracellular interactions with IL-1b.…”
mentioning
confidence: 99%